1987
DOI: 10.1007/bf01314428
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesvirus type 1 gp87 mediates both attachment of virions to susceptible cells and hemagglutination

Abstract: The 87,000-dalton glycoprotein (gp87) of bovine herpesvirus type 1 (BHV-1) was found to selectively attach to susceptible cells. The attachment of gp87 to the cells was markedly decreased by the prior adsorption of intact virions. Anti-gp87 (site Ia) monoclonal antibody, which inhibited BHV-1 adsorption to the cells and neutralized the virus without complement [Okazaki et al., Virology 250: 260-264], was effective in inhibiting the adsorption of gp87. Only the same antibody was able to inhibit the hemagglutina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…These results strongly confirm our previous finding that the hemagglutinin subunit might be associated with a 59 kDa gp [4]. Consequently, it appears that the FHV-1 hemagglutinin also includes an important VN epitope, just as the bovine herpesvirus type 1 hemagglutinin has been identified to be the protein responsible for attachment to susceptible cell [8].…”
supporting
confidence: 90%
“…These results strongly confirm our previous finding that the hemagglutinin subunit might be associated with a 59 kDa gp [4]. Consequently, it appears that the FHV-1 hemagglutinin also includes an important VN epitope, just as the bovine herpesvirus type 1 hemagglutinin has been identified to be the protein responsible for attachment to susceptible cell [8].…”
supporting
confidence: 90%
“…These findings suggest that N polypeptide of PRRSV is playing an extrimely important role in HA activity of PRRSV. Although elucidation of the mechanisms of HA activity of PRRSV will be required in the further studies, it is worthy of note that the HAin of PRRSV is strikingly different from those of orthomyxoviruses, paramyxoviruses and herpesviruses, which are considered to be a part of virion envelope responsible for adsorption of the viruses on the host cells to initiate virus infection (3,6,8,14,18,22).…”
Section: Discussionmentioning
confidence: 99%
“…The disease is characterized by severe reproductive failure in sows and gilts, pneumonia in nursery and young growing pigs, and an increase in preweaning mortality [2,12,15,18]. We have reported that PRRSV agglutinates mouse erythrocytes and the hemagglutination (HA) reaction is inhibited by specific antiserum [4].…”
mentioning
confidence: 99%
“…It has been reported that the gIII of bovine herpesvirus type 1 [14,16] and the gp60 of feline herpesvirus type 1 [7,8] are their respective hemagglutinins, and that they also contain important epitopes for virus neutralization. Previously, we demonstrated CHV-specific hemagglutination activity against dog erythrocyte [12].…”
Section: Discussionmentioning
confidence: 99%